Towards background-free studies of capture reactions in a heavy-ion storage ring. Issue 23 (January 2020) - Varga, L; Blaum, K; Davinson, T; Glorius, J; Jurado, B; Langer, C; Lederer-Woods, C; Litvinov, Yu A; Reifarth, R; Slavkovská, Z; Stöhlker, T; Woods, P J; et al.
Synopsis: Stored and cooled highly-charged ions offer unprecedented capabilities for precision studies in realm of atomic-, nuclear-structure and astrophysics. In context of the latter, after the successful investigation of the cross section of 96 Ru(p, γ) in 2009, in 2016 the first measurement of the 124 Xe(p, γ) 125 Cs reaction was performed at the Experimental Storage Ring (ESR) at GSI.